Entrepreneurial well-being and performance: antecedents and mediators - Tisu, Luca; Vîrgă, Delia; Taris, Toon (Frontiers in Psychology, 2023)
Entrepreneurial well-being is tied to increasing firm performance because entrepreneurs possess additional resources to invest in their businesses. However, research integrating antecedents, specific mechanisms related to the emergence of entrepreneurial well-being (EWB), and performance is scarce. Furthermore, the collective impact of their roles as entrepreneurs and individuals outside the work context is yet to be investigated concerning venture performance. The present study addresses these issues by presenting and testing a comprehensive model employing entrepreneurs' psychological capital as an antecedent of EWB and, indirectly, performance. We investigate this relationship through a serial mediation mechanism enabled by work engagement and entrepreneurial satisfaction regarding entrepreneurs' work roles. Also, we employ work-life balance and mental health as mediators regarding their home roles. Drawing on data from 217 Romanian entrepreneurs, structural equation modeling analyses supported our model. PsyCap was a precursor of entrepreneurial satisfaction both directly and through work engagement. Also, PsyCap predicted entrepreneurs' mental health directly and through work-life balance.